O Processamento referencial na progressão do texto falado - Chagas, Carmen Elena das (2008)
To construct enunciated linguistically or, in sensible ampler, the text, means to give form and linguistics organization to a content, an idea, at last, to a communicative intention, what it allows to say that in the linguistics construction of the statement, activities of referencing are developed. In this direction, to construct the said text is to develop the planning to it, in the measure where evolutes reconstruction process. As a structurally organized activity, the conversation reveals coherent to the ratio that the relation is evidenced, conferring a continuity content. Based on the Textual Linguistics theoretical framework and Discourse Analysis under the optics of the Referencing, this study considers investigating the progression activities of the said text. The corpus for research is provenience of 03 hours recording made in the year of 2005, by means of interaction face to face and if constitutes of an inquiry formed for a documenter and 30 speakers, whose age band it is of the 15 to the 17 years, attending a course the 9th grade of the Basic Education of a Municipal Public School in Quissamã / RJ.